PCT/ALB Ratio in Initial Three days for the Prediction of Secondary Infection in Septic Patients - Zhang C; Huang G; Li H; Zhang T; Jian M; Huang C; Zhang Y; Wang Z; Hou X; Xia Y; Jiang W (Infection and Drug Resistance)
Chunmei Zhang,1,* Guoge Huang,2,* Haizhong Li,1,3,* Tiancao Zhang,1 Mengling Jian,1 Chunyang Huang,1 Yingqin Zhang,1,4 Zheng Wang,5 Xun Hou,1 Yuanyuan Xia,6 Wenqiang Jiang1,7 1Emergency Intensive Care Unit, Department of Emergency Medicine, Guangdong Provincial People’s Hospital (Guangdong Academy of Medical Sciences), Southern Medical University, Guangzhou, Guangdong, People’s Republic of China; 2Department of Emergency Medicine, People’s Hospital of Longhua, Shenzhen, Guangdong, People’s Republic of China; 3Department of Emergency, Boai Hospital of Zhongshan, Zhongshan, Guangdong, People’s Republic of China; 4School of Medicine, South China University of Technology, Guangzhou University City, Guangzhou, Guangdong, People’s Republic of China; 5Guangdong Cardiovascular Institute, Guangdong Provincial People’s Hospital, Guangdong Academy of Medical Sciences, Guangzhou, Guangdong, People’s Republic of China; 6Medical Oncology Department, The Fifth Affiliated Hospital of Guangzhou Medical University, Guangzhou Medical University, Guangzhou, Guangdong, People’s Republic of China; 7Emergency Intensive Care Unit, Department of Emergency Medicine, Guangdong Provincial People’s Hospital (Guangdong Academy of Medical Sciences), Southern Medical University; Guangdong Cardiovascular Institute, Guangdong Provincial People’s Hospital,Guangdong Academy of Medical Sciences, Guangzhou, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wenqiang Jiang; Yuanyuan Xia, Email jiangwenqiang@gdph.org.cn; xiayuany1021@163.comBackground: Procalcitonin (PCT) to albumin (ALB) ratio (PAR) in initial three days is a rapidly available indicator to assess the prognosis of patients with sepsis. This study aims to explore the correlation between changes in PAR during the initial 72 hours and the incidence of secondary infections.Methods: A total of 147 patients with sepsis were included in this study. Patients divided into secondary infection and without secondary infection group, according to whether they had secondary infection. PAR was calculated as serum PCT (ng/mL)/ALB (mg/mL). All statistical analyses were performed using the statistical package SPSS 20.0.Results: Compared with the without secondary infection group, the median APACHE II (22[17– 30] vs 16[11– 25]; p=0.009) were significantly higher in the secondary infection group. And the median ΔPCT/ALB adm-72h (0.10[0.02– 0.48] vs 0.17[0.03– 0.65]; p=0.011) were significantly lower in the secondary infection group. On multiple logistic regression, lower ΔPCT/ALB adm-72h was independently associated with the secondary infection. Decreasing quartile of ΔPCT/ALB adm-72h was statistically significantly associated with secondary infection, particularly among survivors.Conclusion: The decline in the PCT/ALB ratio over the initial 72 hours of the acute phase of sepsis serves as an association for the onset of secondary infections during a septic patient’s hospitalization.Keywords: sepsis, PCT, secondary infection, biomarker